Pengaruh Komitmen Afektif, Kepuasan Kerja, dan Perceived Organizational Support Terhadap Retensi Karyawan Pada PT. Hamasah Konstruksi Indonesia - Imam Zuhri; Tyna Yunita; Muhammad Asif Khan (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the influence of affective commitment, job satisfaction, and perceived organizational support on employee retention at PT. Hamasah Konstruksi Indonesia. The construction industry is known for its high turnover rate, which impacts operational efficiency, project continuity, and human resource costs. Therefore, understanding organizational dynamics is crucial in designing effective retention strategies.This research employs a quantitative approach using a survey method by distributing questionnaires to employees of PT. Hamasah Konstruksi Indonesia. The population consists of 300 employees, with sampling carried out purposively. Data analysis is conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method to test the relationships among variables.The results of the study indicate that affective commitment, job satisfaction, and perceived organizational support have a positive and significant effect on employee retention. Affective commitment emerges as the most dominant factor influencing employees’ intention to remain with the organization. Job satisfaction and perceived organizational support are also proven to enhance employee loyalty and engagement.